PENERAPAN SISTEM AUTOMASI DALAM PENGOLAHAN BAHAN PUSTAKA DI SD MUHAMMADIYAH 2 PONTIANAK - Anggraini, Dian; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstracThe title of this final project is "Application of Library Automation System in the Management of Library Materials in Pontianak Muhammadiyah 2 Elementary Library". The problem that is the focus of the discussion of this paper is the application of automation in the management of library materials. The research used in the preparation of this final project is a descriptive method with a qualitative approach. Data collection techniques are by observation, interviews, and documentation. The results of this study note that to implement the automation system in the management of library materials in Muhammadiyah 2 Elementary School in Pontianak is very necessary because it is to facilitate librarians in managing library materials in the library of Muhammadiyah 2 Elementary School in Pontianak. and it is useful to improve quality not only that the role of librarians is also very needed as the person who performs the atay that runs the bibliography processing automation. Â Keywords: System, Automation, Management, Library SchoolÂ